PENGEMBANGAN KOMPETENSI PEMBURU LEBAH DALAM PEMANENAN LESTARI DAN BERKELANJUTAN MADU APIS DORSATA DI TAMAN NASIONAL GUNUNG RINJANI - Erwan, Erwan; Sukarne, Sukarne; Muhsinin, Muhammad; Herlambang, Dany Alfian (Jurnal Pepadu, 2025)
Indonesia's tropical forests, especially in the Gunung Rinjani National Park (TNGR) area, play an important role in supporting biodiversity and the welfare of local communities. However, the traditional harvesting of forest bee honey (Apis dorsata) often does not take into account the principles of ecological sustainability, which has the potential to damage bee habitat. This activity aims to develop the technical and ecological competence of bee hunters through conservation-based training, which integrates local wisdom with scientific approaches. The method used is Participatory Rural Appraisal (PRA), with a participatory approach in five stages: socialization, training, technology application, mentoring, and evaluation. The results of the activity showed an increase in technical capacity, ecological understanding, and changes in the behavior of bee hunters towards more environmentally friendly harvesting practices. The implication of this activity is the creation of a sustainable honey harvesting model, which not only conserves bee habitat but also increases the economic income of local communities. Keywords: Honey harvesting, Ecological sustainability, Apis dorsata, Conservation, Mount Rinjani National Park